Row Sport Context in PISA Like Mathematics Problem - Arvin Efriani; Ratu Ilma Indra Putri; Hapizah Hapizah (Intelektual Pustaka Media Utama, 2018)
The aim of research was to produce valid, practical and had potential-effect to mathematic literacy ability in PISA like mathematics problem in using row sports context at Asian Games 2018. The research method used development research with development studies type. The subjects of the research were the students with 15 years old of class X SMAN 10 Palembang. The techniques of collecting data were used documentation, walkthrough, test, and interview. This research produced the problem about how the students determined how many benches could be made by only knowing length and width of the boats. The results showed that the problem developed (1) valid from the suitability with the framework PISA regarding content, context, literacy process and level of questions that was connected problems with daily life accordance experts review and one to one stage (2) practical because the problem could be understood by students accordance small group stage, and (3) had a potential effect from the result of analyze the student’s answer in mathematical literacy ability with representation and reasoning ability as dominant accordance field test stage.